Micro-X-Ray Fluorescence, Micro-X-Ray Absorption Spectroscopy, and Micro-X-Ray Diffraction Investigation of Lead Speciation after the Addition of Different Phosphorus Amendments to a Smelter-Contaminated Soil - Baker, Lucas R.; Pierzynski, Gary M.; Hettiarachchi, Ganga M.; Scheckel, Kirk G.; Newville, Matthew (My University, 2014)
The stabilization of Pb on additions of P to contaminated soils and mine spoil materials has been well documented. It is clear from the literature that different P sources result in different efficacies of Pb stabilization in the same contaminated material. We hypothesized that the differences in the efficacy of Pb stabilization in contaminated soils on fluid or granular P amendment addition is due to different P reaction processes in and around fertilizer granules and fluid droplets. We used a combination of several synchrotron-based techniques (i.e., spatially resolved micro-X-ray fluorescence, micro-X-ray absorption near-edge structure spectroscopy, and micro-X-ray diffraction) to speciate Pb at two incubation times in a smelter-contaminated soil on addition of several fluid and granular P amendments. The results indicated that the Pb phosphate mineral plumbogummite was an intermediate phase of pyromorphite formation. Additionally, all fluid and granular P sources were able to induce Pb phosphate formation, but fluid phosphoric acid (PA) was the most effective with time and distance from the treatment. Granular phosphate rock and triple super phosphate (TSP) amendments reacted to generate Pb phosphate minerals, with TSP being more effective at greater distances from the point of application. As a result, PA and TSP were the most effective P amendments at inducing Pb phosphate formation, but caution needs to be exercised when adding large amounts of soluble P to the environment.
Citation: Baker, Lucas R., Gary M. Pierzynski, Ganga M. Hettiarachchi, Kirk G. Scheckel, and Matthew Newville. “Micro-X-Ray Fluorescence, Micro-X-Ray Absorption Spectroscopy, and Micro-X-Ray Diffraction Investigation of Lead Speciation after the Addition of Different Phosphorus Amendments to a Smelter-Contaminated Soil.” Journal of Environmental Quality 43, no. 2 (2014): 488–97. https://doi.org/10.2134/jeq2013.07.0281.
Keywords: Micro-X-Ray fluorescense; Micro-X-Ray absorption spectroscopy; Micro-X-Ray diffraction; Lead speciation; Phosphorus amendments; Smelter-contaminated soil